2020
DOI: 10.1038/s41598-020-77984-1
|View full text |Cite
|
Sign up to set email alerts
|

The variability of functional MRI brain signal increases in Alzheimer's disease at cardiorespiratory frequencies

Abstract: Biomarkers sensitive to prodromal or early pathophysiological changes in Alzheimer’s disease (AD) symptoms could improve disease detection and enable timely interventions. Changes in brain hemodynamics may be associated with the main clinical AD symptoms. To test this possibility, we measured the variability of blood oxygen level-dependent (BOLD) signal in individuals from three independent datasets (totaling 80 AD patients and 90 controls). We detected a replicable increase in brain BOLD signal variability in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 41 publications
3
44
0
Order By: Relevance
“…This system plays a very important role in the removal of harmful metabolites, including Aβ, tau protein and α-synuclein, tissue fluid replacement, and nutrient delivery (Jessen et al, 2015 ). Studies conducted in recent years have shown disturbances in the flow of CSF in the glymphatic system in patients with AD (Tuovinen et al, 2020 ). These alterations were mainly caused by the weakening of intracranial cardiovascular pulsation and correlated with the severity of cognitive dysfunction.…”
Section: Potential Mechanism Underlying the Particle-induced Detrimental Effects On The Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…This system plays a very important role in the removal of harmful metabolites, including Aβ, tau protein and α-synuclein, tissue fluid replacement, and nutrient delivery (Jessen et al, 2015 ). Studies conducted in recent years have shown disturbances in the flow of CSF in the glymphatic system in patients with AD (Tuovinen et al, 2020 ). These alterations were mainly caused by the weakening of intracranial cardiovascular pulsation and correlated with the severity of cognitive dysfunction.…”
Section: Potential Mechanism Underlying the Particle-induced Detrimental Effects On The Cnsmentioning
confidence: 99%
“…As exposure to PM has the greatest negative impact on the respiratory and cardiovascular systems (Kim et al, 2017 ; Ain and Qamar, 2021 ), also indirectly influences the glymphatic system, contributing to the accumulation of incorrectly folded proteins in the brain, which may intensify neurodegenerative changes. This indirect effect of PM on the glymphatic system and neurodegenerative processes is still poorly understood and is the subject of further research, especially since the non-invasive assessment of the glymphatic system function using the fMRI method may allow for a relatively early diagnosis of neurodegenerative disorders, including AD (Tuovinen et al, 2020 ).…”
Section: Potential Mechanism Underlying the Particle-induced Detrimental Effects On The Cnsmentioning
confidence: 99%
“…12 A recent study also showed increased fMRI signal variability at cardiorespiratory frequencies in Alzheimer's disease patients when compared to cognitively normal performing older adults. 34 This study aimed to determine whether BOLD signal fluctuations as quantified by the amplitude of low-frequency fluctuations (ALFF) in the range of 0.01-0.08 Hz are related to brain Aβ deposition in patients with amnestic mild cognitive impairment. 4,[35][36][37][38] Furthermore, we examined whether the associations between local ALFF and brain Aβ depositions are influenced by the estimated upper-stream cerebrovascular hemodynamics, spontaneous neuronal activities, or both, using the well-established signal regression approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of systemic arterial flow may avoid CSF stagnation at the perivascular spaces, while implantable pump methods can regulate the CSF pulsatility by volume changes in low blood flow situations in the canine (Luciano et al, 2017 ). On the venous side, the search and correction of possible causes of intracranial venous hypertension (Wilson, 2016 ), including hepatic (Gallina et al, 2019b ; Hadjihambi et al, 2019 ) and pulmonary dysfunctions (Gallina et al, 2020 ; Kananen et al, 2020 ; Russ et al, 2020 ; Tuovinen et al, 2020 ), may prevent or restore a reduction of the blood brain flow and facilitate CSF circulation. Moreover, CSF drainage may reverse venous hypertension, restoring interstitial fluid circulation (Wilson, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Primary noxae are the genetic aquaporin-4 channelopathies (Rainey-Smith et al, 2018 ) or auto-antibodies that directly damage aquaporin-4 (Papadopoulos and Verkman, 2013 ). Secondary noxae are the derangements of the intra-extra cranial hydrodynamic at various levels leading to CSF circulation alterations (Wilson, 2016 ; Tuovinen et al, 2020 ; Rajna et al, 2021 ). CSF flow waves, hemodynamic, and neuronal electrical activity oscillations connect in sleep (Fultz et al, 2019 ).…”
Section: Opinionmentioning
confidence: 99%